NMR spectroscopy in inorganic chemistry - Iggo, Jonathan A; Oxford University Press (Oxford ; New York : Oxford University Press, 2007)
Written with the needs of students in mind, this series of short texts provides accessible accounts of essential topics in chemistry and chemical engineering
Fundamentals -- Structure determination -- Dynamic processes and NMR -- Solid state
Includes bibliographical references and index
Keywords: Nuclear magnetic resonance spectroscopy; Inorganic compounds